Polarized Color Filters Using Colloidal Quantum Rod Nanocrystals for Advanced High‐Performance Displays - Jianxin Song; Maksym F. Prodanov; Yiyang Gao; Chengbin Kang; Debjyoti Bhadra; Yuechu Cheng; Zebing Liao; Kumar Mallem; Vigneshwaran Swaminathan; Valerii V. Vashchenko; Xiao Wu; Xinhui Lu; et al. (Advanced Science)
Abstract In this article, color filters (CFs) emitting linearly polarized light, achieving both full‐color and pixel‐level precision, which can simultaneously offer high color saturation, high ambient contrast ratio (ACR), and high efficiency for modern displays, are disclosed. The quantum rods (QRs) exhibit a narrow‐band polarized emission that effectively mitigates traditional challenges of color purity and light losses. Specially designed ligands on the QR surfaces allow higher load of the QR material into the polymer matrix with uniform alignment. Optimizing inkjet printing, photolithography, and photoalignment processes, a remarkable degree of polarization (DOP) of 0.65 is achieved for precisely patterned red and green QR CFs. Due to the polarized emission of unidirectionally aligned QRs, the liquid crystal display (LCD) equipped with the designed QRCF shows enhanced efficiency and ACR, highlighting advantages for their application in next‐generation displays over other types of photoluminescence CFs.